IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY PT. SURYA BINTANG INDONESIA (Studi Kasus Desa Karang Endah Kecamatan Lengkiti) - Candan Rivando; Yahnu Wiguno Sanyoto; Eva Susanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2026)
PT Surya Bintang Indonesia, an oil palm company operating in Karang Endah Village, Lengkiti District, Ogan Komering Ulu Regency, is required to implement Corporate Social Responsibility (CSR) as a form of the company’s responsibility toward social, economic, and environmental development in its surrounding operational area. However, in practice, a gap was found between the planned CSR programs and their actual implementation, and the implementation process still faces several problems. This study examines the success of CSR implementation at PT SBI using the policy implementation theory of Mazmanian and Sabatier, with three main focuses: problem characteristics, the ability of policy to structure implementation, and nonstatutory variables across three aspects: economic, social, and environmental. This study employed a descriptive qualitative method through in-depth interviews, observation, and documentation. The findings show different levels of success across the three aspects. The economic and environmental aspects were considered moderately successful through the absorption of casual daily workers, oil palm seed assistance, road maintenance, and culvert installation, while the social aspect has not yet been realized because education and basic health programs are still at the proposal stage. The analysis identifies the main governance problems as low information transparency, less-than-optimal participation from the Village Consultative Body and youth groups, and the absence of a documented complaint mechanism, which contributed to the failure of social program realization. This study recommends improving transparency, strengthening stakeholder participation, implementing priority social programs, and establishing a documented complaint mechanism.